Localized Ištar Goddesses and the Making of Socio-Political Communities: Samsi-Addu’s Eštar Irradan at Mari - Knott, Elizabeth (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
The goddess Eštar Irradan is one of the many Ištar-type goddesses that populate the textual records of Mari (Tell Hariri) during the Old Babylonian period (ca. 1800-1600 BC). Yet this goddess has a particular history that associates her more closely with the passing ruler Samsi-Addu than the city itself. Textual references indicate that Eštar Irradan was associated with a location outside of Mari – probably the eastern city of Ekallatum, a city most likely located in the vicinity of Aššur on the Tigris River, and home to Samsi-Addu. First appearing in ritual and administrative records dated to the period in which Samsi-Addu controlled Mari (ca. 1792-1775 BC), Eštar Irradan’s presence in the palace’s documentation disappears during the reign of Zimri-Lim (ca. 1775-1764 BC). In this article, I propose that localized Ištar goddesses like Eštar Irradan were often invoked to construct and amplify social and political ties across space.